Influence of UHMWPE on the expansion characteristics of expansive soil: Experimental studies - Yonggang Huang; Hongri Zhang; Rong Shen; Xianliang Tan; Xinzhong Wang; Yuexing Wu (PLoS ONE, 2025)
This paper investigates the effectiveness of using Ultra-High-Molecular-Weight Polyethylene (UHMWPE) Fiber to improve expansive soil. The test results indicate that the amount and length of UHMWPE significantly affect the swelling pressure and free swelling ratio of the reinforced soil. The swelling pressure of reinforced expansive soil exhibits a significant negative correlation with both the UHMWPE content (p < 0.05) and its length. The free swelling ratio of reinforced expansive soil was significantly negatively correlated with both the content (p < 0.05) and length of UHMWPE. When the UHMWPE content exceeds 0.3% the weight of the soil, there is no significant decrease in the swelling pressure of the reinforced soil (p = 0.052, close to the threshold of significance). When the length of UHMWPE is greater than 9 mm, there is no significant decrease in the free swelling ratio of the reinforced soil (p = 0.165). Thus, it is recommended to use 0.3% UHMWPE with a length of 9 mm for optimal results. Swelling pressure, free swelling ratio and fiber content follow a quadratic polynomial relationship. While, the relationship between swelling pressure and fiber length is linear. The relationship between free swelling ratio and fiber length is a power function.